2018
DOI: 10.1371/journal.pone.0193498
|View full text |Cite
|
Sign up to set email alerts
|

In vitro immunotherapy potency assays using real-time cell analysis

Abstract: A growing understanding of the molecular interactions between immune effector cells and target tumor cells, coupled with refined gene therapy approaches, are giving rise to novel cancer immunotherapeutics with remarkable efficacy in the clinic against both solid and liquid tumors. While immunotherapy holds tremendous promise for treatment of certain cancers, significant challenges remain in the clinical translation to many other types of cancers and also in minimizing adverse effects. Therefore, there is an ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 47 publications
4
65
0
Order By: Relevance
“…As described in Figure 5(B), there was a dose-or time-dependent suppression of survival of CAL27 cells induced by Co-SLD varying from 5 to 20 lM. KT50 (the amount of time it takes to kill 50% of the target tumour cells) was selected as a quantitative parameter for evaluating the efficient killing kinetic of Co-SLD [68]. KT 50 values were roughly 63, 41 and 13 h, in CAL27 cells exposed to 5, 10, and 20 lM, respectively.…”
Section: Inhibition Of Cell Growth Induced By Co-sldmentioning
confidence: 99%
“…As described in Figure 5(B), there was a dose-or time-dependent suppression of survival of CAL27 cells induced by Co-SLD varying from 5 to 20 lM. KT50 (the amount of time it takes to kill 50% of the target tumour cells) was selected as a quantitative parameter for evaluating the efficient killing kinetic of Co-SLD [68]. KT 50 values were roughly 63, 41 and 13 h, in CAL27 cells exposed to 5, 10, and 20 lM, respectively.…”
Section: Inhibition Of Cell Growth Induced By Co-sldmentioning
confidence: 99%
“…In an elegant approach, Lee et al started their search for a potency marker to predict BM‐MSCs’ efficacy to treat sterile inflammations comparing more efficacious to less efficacious MSC preparations together with gain‐of‐function experiments, which led to the discovery of TNF‐α–stimulated gene‐6 as a biomarker that identifies MSC preparations with potent anti‐inflammatory properties. A cytolytic immunopotency assay using impedance to measure the viability of target tumor cells affected by immunotherapeutic interventions was introduced . Killer et al reported that MSCs cocultured with immune cells increased their glycolytic and respiratory activity, and this enhanced cell metabolism was accompanied by higher T‐cell suppressive capacities of MSCs.…”
Section: Quality Controlmentioning
confidence: 99%
“…24 After culturing SKOV3 cells or HER2tumor cells (10 4 cells per well) in E-plate 96 (ACEA Bioscience) for approximately 24 hours, pretreated CAR-T cells with or without 100 ng/mL IL-18 were added to the plates (E:T = 5). This cell detection technology is based on the microelectronic impedance technology, and the size of impedance depends on the number, size and shape of the adherent cells, and the quality of the cell-substrate attachment.…”
Section: Real-time Cytotoxicity Assays (Rtca)mentioning
confidence: 99%
“…This cell detection technology is based on the microelectronic impedance technology, and the size of impedance depends on the number, size and shape of the adherent cells, and the quality of the cell-substrate attachment. 24 After culturing SKOV3 cells or HER2tumor cells (10 4 cells per well) in E-plate 96 (ACEA Bioscience) for approximately 24 hours, pretreated CAR-T cells with or without 100 ng/mL IL-18 were added to the plates (E:T = 5). Data were acquired and analyzed according to the protocols specified by the manufacturers (ACEA Bioscience, Inc. RTCA Software 2.1).…”
Section: Real-time Cytotoxicity Assays (Rtca)mentioning
confidence: 99%